Mechanics of aircraft structures - Sun, C. T. (Chin-Teh) 1939- (John Wiley & Sons, 2006)
Mechanics of Aircraft Structures, Second Edition is the revised update of the original bestselling textbook about aerospace engineering. This book covers the materials and analysis tools used for aircraft structural design and mechanics in the same easy to understand manner. The new edition focuses on three levels of coverage driven by recent advances in industry: the increase in the use of commercial finite element codes require an improved capability in students to formulate the problem and develop a judgement of the accuracy of the numerical results; the focus on fracture mechanics as a tool in studying damage tolerance and durability has made it necessary to introduce students at the undergraduate level to this subject; a new class of materials including advanced composites, are very different from the traditional metallic materials, requiring students and practitioners to understand the advantages the new materials make possible. This new edition will provide more homework problems for each chapter, more examples, and more details in some of the derivations.